1997
DOI: 10.1016/s0140-6736(97)01004-0
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-node biopsy to avoid axillary dissection in breast cancer with clinically negative lymph-nodes

Abstract: In the large majority of patients with breast cancer, lymphoscintigraphy and gamma-probe-guided surgery can be used to locate the sentinel node in the axilla, and thereby provide important information about the status of axillary nodes. Patients without clinical involvement of the axilla should undergo sentinel-node biopsy routinely, and may be spared complete axillary dissection when the sentinel node is disease-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
667
2
33

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,821 publications
(718 citation statements)
references
References 15 publications
16
667
2
33
Order By: Relevance
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, a tumour-free sentinel lymph node implies the absence of lymph node metastases in the entire lymphatic basin. This sentinel node concept had been previously confirmed by H&E examinations, immunohistochemical study and nonquantitative RT -PCR assays (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998;Kataoka et al, 2000;Manzotti et al, 2001;Branagan et al, 2002;Ishida et al, 2002).…”
mentioning
confidence: 62%
“…In addition, no post-PCR manipulations are required with this method, and quantification and calculation of the results are all automated. Currently, many investigators reported sentinel lymph node biopsy for the diagnosis of axillary lymph node metastases from breast cancer (Giuliano et al, 1994;Albertini et al, 1996;Veronesi et al, 1997;Krag et al, 1998). The sentinel lymph node is the first lymph node to receive drainage from the primary tumours in early stage cancers (Morton et al, 1992).…”
mentioning
confidence: 99%
“…More recently, sentinel lymph node biopsy (SLNB) has been proposed as an alternative method for staging the axilla in women who have early breast cancer with clinically node negative axillae (Giuliano et al, 1994;Veronesi et al, 1997;McIntosh and Purushotham, 1998;Veronesi et al, 1999;Veronesi et al, 2003). The SLN is the first lymph node to receive lymphatic drainage from a tumour.…”
mentioning
confidence: 99%
“…[1][2][3] The technique identifies a sentinel lymph node or nodes in the axilla of a patient with breast carcinoma using a vital dye or radionuclide. If the sentinel lymph node is negative for malignancy, the patient can forego regular axillary lymph node dissection, since the probability that the additional dissected lymph nodes will contain metastatic tumor when the sentinel node is negative is about 5%.…”
mentioning
confidence: 99%